472 Effects of Recurrent Mild Traumatic Brain Injuries on Incidence, Severity, and Recovery of Concussion in Young Student-Athletes. (1st April 2022) - Hannah, Theodore; Spiera, Zachary; Li, Adam Y.; Dreher, Nickolas; Ali, Muhammad; Marayati, Naoum F.; Lovell, Mark R.; Choudhri, Tanvir
Abstract : INTRODUCTION: Currently, it is known that athletes who sustain recurrent concussions are at an increased risk for long-term neurological consequences. Moreover, in the short term, athletes with a history of concussions are significantly more likely to sustain future concussions. Although the increased incidence of mTBI among athletes with a history of concussions has been well documented, there is less consensus about how recurrent concussions affect the severity and recovery of the next head trauma. METHODS: Data from 11 563 ImPACT baseline evaluations of US student-athletes aged 12 to 22 years were separated into 2 cohorts: subjects reporting 2 or more previous concussions (PC; n = 976 baseline evaluations) at baseline and a control group reporting zero previous concussions (CT; n = 7743 baseline evaluations). Subjects reporting 1 prior concussion were excluded. Differences in SND incidence, severity, and recovery between the 2 cohorts were assessed using chi-squared tests, t tests, survival analyses, and multivariate regressions. RESULTS: The PC cohort had a higher incidence of head injury leading to ImPACT (436.7 per 1000 person-years vs 194.4 per 1000 person-years, P < .0001) and a higher incidence of SND (140.4 vs 71.8, P < .0001) than controls. However, the Severity Index (SI) demonstrated that SND severity was lower in the PC group (7.55 vs 8.59, P = .04). Adjusted analyses similarly demonstrated that the PC cohort had increased SND incidence (odds ratio = 1.93; 95% CI, 1.61 to 2.31; P < .0001), decreased SI (β = −1.37; 95% CI, −2.40 to −0.34; P = .009), and equivalent recovery (hazard ratio = 0.98; 95% CI, 0.76 to 1.72; P = .90). CONCLUSION: Participants with a history of concussion have a higher incidence of SND but present with lower severity SND, which may be a result of increased concussion education or symptom awareness. Recurrent concussion has no significant impact on acute neurocognitive recovery. Together, these results provide evidence against the supposition that a history of concussion increases the severity of future SND.